Study Construction of Gillnet In The Village Nipah Panjang 1, Subdistrict of Nipah Panjang, East Tanjung Jabung Regency, Province of Jambi - Aliman Sutrisno; Irwandy Syofyan; Isnaniah ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted in November 2013 in the Village of Nipah Panjang 1, District Nipah Panjang, East Tanjung Jabung Regency, Province of Jambi. The method used in the research study construction gillnet fishing gear is a method of survey. The purpose of this study was to compile information about the specifications of gillnet fishing gear operating in the village of Nipah Panjang 1 . After doing research on the net to know that gillnet operated in the village most of the Nipah Panjang 1 has a construction similar to that of the gill nets are generally composed of ris top rope buoy rope , net weight , lower ris rope , buoys , big bouys and sinker . It's just shortening value less than 30 % , while there is a difference in vertices of the mesh gillnet use this is caused from the characteristics of the material . If the materials used PA multifilament englis knot used for the passage of knots and knot using monofilament double englis knot because the danger of a more slippery surface.Keywords: Contruction, Gillnet, Jambi